2010
DOI: 10.4103/0970-0358.63968
|View full text |Cite
|
Sign up to set email alerts
|

Marginal mandibular branch of the facial nerve: An anatomical study

Abstract: Smile is one of the most natural and important expressions of human emotion. Man uses his lips mainly to register his emotions. Thus, the slightest asymmetry or weakness around the lips and mouth may transform this pleasant expression into embarrassment and distortion. The circumoral musculature, the major part of which is supplied by the marginal mandibular branch of the facial nerve, is the main factor in this expression. Therefore, an injury to this nerve during a surgical procedure can distort the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 11 publications
2
43
0
1
Order By: Relevance
“…The intricate anatomic division pattern of the facial nerve, the dramatic deformities consequentially from its injury and its decisive role in facial expressions have enthused numerous anatomic and exploratory studies on the nerve. [1][2][3] The choice of the surgical approach is very linked to the parotid surgery because the practical significance of the branches of facial nerve and the intense anatomic randomness of the parotideal area. 4 The facial nerve emerges from the base of the skull at the stylomastiod foramen.…”
Section: Introductionmentioning
confidence: 99%
“…The intricate anatomic division pattern of the facial nerve, the dramatic deformities consequentially from its injury and its decisive role in facial expressions have enthused numerous anatomic and exploratory studies on the nerve. [1][2][3] The choice of the surgical approach is very linked to the parotid surgery because the practical significance of the branches of facial nerve and the intense anatomic randomness of the parotideal area. 4 The facial nerve emerges from the base of the skull at the stylomastiod foramen.…”
Section: Introductionmentioning
confidence: 99%
“…This result is similar to that of Yang et al (2016) (21) carried out on 29 hemifaces who reported that in 82.8% of cases the MMB was less than 5 mm below the angle of the mandible and in 89.7% of the MMB was less than 10 mm below the angle of the mandible. However, the results of Batra et al (2010) (15) are different MMB 52% along the mandibular angle and 16% in the latter.…”
Section: Relation Of the Mmb With The Angle Of The Mandiblementioning
confidence: 65%
“…This involves searching for the MMB before its intersection with the facial vein, whether before point X, which further reduces the locating area. The study by Batra et al (2010) (15) made on 50 hemifaces human cadavers joins our study and describes the marginal branch of the mandible as a single branch to its origin in 88% of cases, 92% during the course, but It rarely single branch at termination (4% of cases).The MMB was divided into two branches in 12% of the cases at its origin, 8% of cases during the course and 12% of the cases at its termination. In almost all anatomical subjects (84% of cases) the MMB had more than two branches at its termination.…”
Section: The Marking Triangle Of the Marginal Branch Of The Mandiblementioning
confidence: 91%
See 2 more Smart Citations